STRATEGI PENJUALAN PERUMAHAN SUATU TINJAUAN TEORITIS - St. Rukiah (AkMen JURNAL ILMIAH, 2016)
The company developer as a company that is engaged in the construction of a residential area and the settlement of a particular location, a lot of coloring improve the livelihoods of communities, particularly in Makassar. presence and gait developers often used as a measure to measure the temperature of the economy and monetary policy in the region. Marketing success is determined by various factors, both internal and external. Internal factors related to the sales system with a wide range of company policy is concerned, while the external factors associated with the environment, competition, and so forth. Residential business (real estate) is currently berkembag very rapidly along with the development of society faster and more advanced as a result of the progress of human civilization internationally dikeanl with globalization. Company housing sector (real estate) as well as the rapidly growing needs of the community, so that new settlements expanding, it is due to the ever increasing population growth.